IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 08 TAHUN 2014 TENTANG PENGELOLAAN SAMPAH (STUDI TENTANG FORUM MASYARAKAT PEDULI SAMPAH) - Yudi Anugerah Purwadi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is motivated by not yet optimal role of Community Forum About Garbage in Pekanbaru city. Dinas Kebersihan dan Tata Kota Pekanbaru Not yet optimal to implement the Perda Pekanbaru No. 8 of 2014, especially Article 40. Therefore researchers want to review the implementation and inhibiting factors of implementation of article 40 of Local Regulation No. 8 Pekanbaru City. The method used in this research included into qualitative and quantitative research with descriptive approach, of which the sample of research is 74 people, where 2 people as key informants, 14 people as informants, and 58 people as respondents.Based on research results, that: (1) implementation of Regional Regulation of Pekanbaru City Number 08 Year 2014 on Waste Management is a guideline or basis in handling garbage by Sanitation and Garden Service of Pekanbaru City, but for article 40 has not been implemented, because the existing community forum is still limited to RW scope, ie LKM-RW. Where the LKM-RW is only tasked to quote garbage levies, not seek and provide solutions in handling waste problems as contained in pasa 40 Pekanbaru City Regulation No. 08 of 2014 on the Community Forum Peduli Sampah; (2) the inhibiting factor in the implementation of article 40 of Pekanbaru City Regulation No. 08 of 2014 on the Community Forum for Garbage Concern is the lack of socialization of the regulation by the Head of Service, the secretary of the Department to subordinates or the sections and sections in the Sanitation and Gardening Agency of Pekanbaru City, To the community is hampered, although there are planning activities for the formation of Community Forum Peduli Sampah before, but the realization has not existed until now. If seen from research indicator, hence implementation inhibiting factor is factor of policy content and support factor. Factor The content of the policy is not known to all employees clearly, especially regarding community forums care waste. The support factor is the impact of the ignorance of policy on community forums concerning garbage, so there is no good supportKeywords : Implementation, Regional Regulation